IMPLEMENTATION OF TALENT MANAGEMENT: STRATEGIES FOR RETAINING HIGH POTENTIAL EMPLOYEES IN A COMPETITIVE ERA - Hendra Kurniawan; Rizkiana Karmelia Shaura (Jurnal Ekonomi, 2023)
This study aims to analyze and understand the implementation of talent management as a strategy to retain high potential employees in a competitive era. In an increasingly competitive business environment, companies are required to ensure that they can retain and maximize the potential of their best employees in order to achieve competitive advantage. This study uses a qualitative method with a descriptive approach. Research results show the benefits of implementing talent management in organizations or companies including having the right people for the right jobs, increasing employee retention, making companies more developed, and making the recruitment process better. Research has also found that retaining highly talented employees can be done by providing clear career development, recognition and appreciation for work results, creating an attractive work environment and providing appropriate compensation.